ANALYSIS OF APPLIED REFERENCE LEADS INFLUENCE ON AN EEG SPECTRUM - Plechawska-Wójcik, Małgorzata; Wesołowska, Kinga; Wawrzyk, Martyna; Kaczorowska, Monika; Tokovarov, Mikhail (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
The article presents the analysis of various kinds of montage applied in the analysis of electroencephalographic data. The present study covers analysis of data obtained as a result of EEG examination of several persons with the age of 23–24 years. Every person has undergone an examination with appliance of 21 electrodes in accordance with classic EEG record method applying the 10–20 system. The examined persons were asked to perform the following activities: sitting steadily with opened eyes, sitting steadily with closed eyes as well as typical cognitive activity i.e. silent reading of given text. Every fragment has been subjected to initial data analysis (filtering, artifact correction) and used for spectral analysis afterwards. The whole analysis has been realized on the basis of four EEG montage examples (two bipolar and two monopolar). For each of them comparative analysis concerning the following points has been carried out: EEG spectra as well as other measures, such as activity maps, diffraction histograms for separate waves and spectrum charts for the selected electrodes.